Virtual Tours as Emerging Technologies to Engage Children and Youth with their Country’s Historical Conflicts - Nicolaidou, Iolie; Zupančič, Rok; Fiedler, Anke; Andresen, Kenneth; Hoxha, Abit; Ntaltagianni, Christina; Aivalioti, Maria; Kasapovic, Mak; Milioni, Dimitra L. (My University, 2022)
Virtual Reality (VR) is increasingly used for visiting historic places. Research on VR experiences in dark tourism (that focuses on mortality) focuses almost exclusively on adults. No studies were found that used virtual tours to engage children with their own country’s conflicts. The present study addresses this gap by designing and developing virtual tours in four cities of Europe with a troubled past. Virtual tours engage children and youth in historical conflicts using multi-perspective storytelling. The aim of this pre-test posttest comparative case study is to examine the change on students’ perceptions of their country’s troubled past after their interaction with a virtual tour of their capital. A secondary aim is to document students’ evaluation of the virtual tour. A questionnaire examining students’ perceptions was completed before and after students’ individual interaction with a virtual tour. Participants included 360 students (212 from Cyprus, 42 from Germany, 63 from Bosnia-Herzegovina and 44 from Kosovo). Findings indicate a statistically significant positive change in perceptions of troubled pasts for primary/secondary students from Cyprus, Bosnia-Herzegovina and Germany. Preliminary results are promising and indicate the effectiveness of virtual tours as tools that can have an effect on students’ perceptions of troubled pasts, particularly for children rather than young adults. Students’ evaluation of the virtual tours was positive, irrespectively of participants’ age, indicating high acceptability.
Keywords: History; Children; Virtual reality; Troubled past; Multiple perspectives; Conflict resolution